Developing and testing a sprayable overlay of strain hardening cement-based composite for retrofitting of unreinforced load bearing masonry walls - De Beer, Leon Roode (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.